2019
DOI: 10.1080/00313831.2019.1623308
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Stress and Students’ School Well-being: the Case of Upper Secondary Schools in Stockholm

Abstract: Stress and stress-related complaints such as fatigue and depressed mood are common among teachers. Yet, knowledge about the links between the overall level of teacher stress within a school and individual student outcomes is scarce. This study investigates if the levels of teacherreported stress, fatigue and depressed mood within a school are associated with students' ratings of their school satisfaction and perceived teacher caring, respectively. Data derives from two separate data collections performed in up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 49 publications
(82 reference statements)
2
60
1
2
Order By: Relevance
“…This association was mediated by students' perception of adults' tendency to intervene when bullying occurs, but not by teachers' overall stress level. In a previous study, we found that higher levels of teacher stress at the school-level were predictive of less perceived teacher caring and lower school satisfaction among students (Ramberg et al, 2019). However, the present study shows no corresponding association with bullying behaviour, indicating that the teachers manage their stress so that it does not influence their ability to monitor the students or otherwise prevent bullying behaviours.…”
Section: Discussioncontrasting
confidence: 84%
“…This association was mediated by students' perception of adults' tendency to intervene when bullying occurs, but not by teachers' overall stress level. In a previous study, we found that higher levels of teacher stress at the school-level were predictive of less perceived teacher caring and lower school satisfaction among students (Ramberg et al, 2019). However, the present study shows no corresponding association with bullying behaviour, indicating that the teachers manage their stress so that it does not influence their ability to monitor the students or otherwise prevent bullying behaviours.…”
Section: Discussioncontrasting
confidence: 84%
“…This will play a particularly important role in the provision of timely interventions. Indeed, the members of group 2 were educational professionals, who are known to experience high levels of stress, which can impact the teaching and learning process and increase their likelihood of developing health problems or absenteeism (Carlotto and Câmara, 2019;Chambers Mack et al, 2019;Gallardo-López et al, 2019;Ramberg et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, student problem behaviors are associated with greater exhaustion and decreased enthusiasm among teachers (Nizielski et al, 2013;Aldrup et al, 2018;Aparisi et al, 2019), which in turn can cause them to abandon the teaching profession (Skaalvik and Skaalvik, 2018;Chambers Mack et al, 2019). The stress that teachers experience can also have negative effects on students (e.g., low levels of student satisfaction) (Ramberg et al, 2019). DE can result in low levels of professional consciousness and PA and cause teachers to be irritable, cynical, and critical; these factors involve psychological problems that can adversely affect the teachinglearning process (Yin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, prevention in primary, secondary or tertiary workplaces is necessary [20,21]. In fact, Group 1 has a high level of burnout, and Group 3 is at-risk, because it has moderate burnout values, and low professional achievement values are worrisome, so it is recommended to start management programs for these symptoms [2,17,18,39], which can lead to consequences even in students [17].…”
Section: Discussionmentioning
confidence: 99%
“…The psychological balance and health of teachers depend on preventing the factors that have been associated with this syndrome [61], which can have consequences even in students [17]. Primary prevention aimed at guaranteeing well-being is essential.…”
Section: Discussionmentioning
confidence: 99%